Do good neighbors lead to lower greenhouse gas emissions across countries? A spatial analysis - Szulczyk, Kenneth Ray; Angelica, Jessy; Tan, Yeng-May (Asian Journal of Economic Modelling, 2025)
This study examines how spatial interdependence helps reduce greenhouse gas (GHG) emissions across 68 countries from 1990 to 2023. The researchers hypothesized that a country’s environmental policies and GHG emissions are influenced by its neighbors, and their findings support this. The study used spatial fixed effects, spatial pooled, and spatial random effects models to analyze the effects of several variables on GHG emissions. The results show that a neighbor’s high GHG emissions can actually help a country lower its own. Furthermore, the study found that energy consumption increases emissions, whereas innovation (patents), renewable energy, and trade openness all decrease them. However, the study found no evidence to support the Environmental Kuznets Curve or the Pollution Haven Hypothesis. The findings emphasize the importance of regional cooperation and the diffusion of public policies and knowledge to combat climate change, aligning with the United Nations’ Sustainable Development Goal 13. The study highlights the vital role of coordination between countries in addressing global warming.